Evaluation of Genotoxicity by Micronucleus Assay in vitro and by Allium cepa Test in vivo - Christina Banti; Sotiris Hadjikakou (Bio-Protocol, 2019)
The in vitro and in vivo genotoxicity of new metallodrugs either as Small Bioactive Molecules (SBAMs) or Conjugates of Metals with Drugs (CoMeDs) is evaluated by the micronucleus test and the Allium cepa assay, respectively. Fetal lung fibroblast cells (MRC-5), normal human corneal epithelial cells (HCEC) and immortalized human keratinocytes cells (HaCaT) were incubated with solutions of SBAMs or CoMeDs at their IC50 values for 48 h (the concentration of a compound which is required to inhibit the cells growth by 50% in relation to the non-treated cells). The micronucleus abundance percentage towards the corresponding one, of the non-treated cells indicates the in vitro genotoxicity of the formulations. The in vivo Allium cepa test comprises the exposing of the plant Allium cepa roots to an SBAMs or a CoMeDs solution for 48 h. The percentages of the mitotic index, the chromosome aberrations, the nuclear abnormalities and the presence of the micronucleus are calculated indicating the in vivo genotoxicity of the agent.